Προστασία ατμοσφαιρικής διάβρωσης Αλουμινίου/Ανοδίωση Al - Παπαχριστοδούλου, Ανδρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Aluminium or aluminum is probably one of the most widely used materials in the world and it is used on many applications for a long period of time. However aluminum is a metal and as so can suffer from corrosion and particularly atmospheric corrosion. Atmospheric corrosion is significant to the economy, in terms of financial costs for corrosion prevention and structural inspection and maintenance, and to society terms of its environmental impact and potential safety issues. There are a number of ways one can protect aluminum against atmospheric corrosion and anodizing is one of them. Anodizing is an electrolytic passivation process used to increase the thickness of the natural oxide layer on the surface of metal parts. Anodizing increases resistance to corrosion and wear. Today the development of technology along with internet use allows everyone to make anodized parts even in their home. An effort of making a small DIY anodizing unit was made in the present dissertation. Furthermore using the ISO 9223:2012 standard a try was made to define the corrosivity of atmosphere of a selected area. Finally from electrochemical corrosion experiment it was possible to determine corrosion resistance and corrosion rate of aluminum in sea water conditions.
Keywords: Aluminium; Atmospheric corrosion; Anodizing; Electrochemical corrosion; Αλουμίνιο; Ατμοσφαιρική διάβρωση; Ανοδίωση; Ηλεκτροχημική διάβρωση